2020
DOI: 10.5194/egusphere-egu2020-18245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semi-privacy and Color Application as Elements of Habitability in Concept Designs for Extra-terrestrial Habitation

Abstract: <p><strong>Introduction<br></strong>Concepts for designs of extra-terrestrial habitats are experiencing a growing importance in the space industry. New technologies and innovative materials bring the need for novel spatial arrangements in these habitats. Two of the most important components to improve habitability in extra-terrestrial habitats - the situation of privacy and color application - have been addressed in a lunar simulation (EMMIHS-II) at the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…found in a 180-day controlled environment life support system that sensory interaction is of great help to the crew's mood and that variability and stability of behaviour are adaptive strategies [18,19]. This was also confirmed by Schlacht (2010 and2012) at [MDRS] [20][21][22][23][24][25]. Furthermore, NASA's Extreme Environment Mission Action [NEEMO] conducted psycho-physiological investigations of interplanetary expeditions at the Antarctic Space Simulation Station and found that the ICE environment provides higher fidelity to dangerous environments, reducing sensory stimulation and resulting in a cumulative stress response, and the photoperiod changes experienced during long spaceflights [26].…”
Section: Introductionmentioning
confidence: 76%
“…found in a 180-day controlled environment life support system that sensory interaction is of great help to the crew's mood and that variability and stability of behaviour are adaptive strategies [18,19]. This was also confirmed by Schlacht (2010 and2012) at [MDRS] [20][21][22][23][24][25]. Furthermore, NASA's Extreme Environment Mission Action [NEEMO] conducted psycho-physiological investigations of interplanetary expeditions at the Antarctic Space Simulation Station and found that the ICE environment provides higher fidelity to dangerous environments, reducing sensory stimulation and resulting in a cumulative stress response, and the photoperiod changes experienced during long spaceflights [26].…”
Section: Introductionmentioning
confidence: 76%